1978
DOI: 10.1042/bj1710559
|View full text |Cite
|
Sign up to set email alerts
|

Surface behaviour of gangliosides and related glycosphingolipids

Abstract: 1. The surface behaviour of six different gangliosides and eight chemically related glycosphingolipids was investigated in monolayers at the air-water interface. 2. Mono-, di-, tri and tetra-hexosylceramides had force-area isotherms showing similar limiting molecular areas on 145 mM-NaCl, pH 5.6. The increasing number of negatively charged sialosyl residues in mono-, di- and tri-sialogangliosides induced a progressive increase in the liquid-expanded character of the films and in the limiting area occupied per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
124
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(143 citation statements)
references
References 18 publications
19
124
0
Order By: Relevance
“…However, the crosssectional area contribution of these gangliosides does not reach values as small as those observed for the molecular area contribution of GM1, namely about 35 Å 2 (Carrer and Maggio 2001), which is about the minimum possible for two closely packed hydrocarbon chains perpendicular to the interface. This is consistent with previous reports indicating that the extended oligosaccharide chain of gangliosides and other GSLs, oriented perpendicularly to the interface (Maggio et al 1978b(Maggio et al , 1981Li et al 2002;Diociaiuti et al 2004), can largely Bfit^under the area of two closely packed hydrocarbon chains. For the more complex oligosaccharide polar head groups, slightly more spacing is required, especially at low surface pressures (Maggio et al 1981;Carrer and Maggio 2001).…”
Section: Ceramide-glycosphingolipid Interactionssupporting
confidence: 93%
“…However, the crosssectional area contribution of these gangliosides does not reach values as small as those observed for the molecular area contribution of GM1, namely about 35 Å 2 (Carrer and Maggio 2001), which is about the minimum possible for two closely packed hydrocarbon chains perpendicular to the interface. This is consistent with previous reports indicating that the extended oligosaccharide chain of gangliosides and other GSLs, oriented perpendicularly to the interface (Maggio et al 1978b(Maggio et al , 1981Li et al 2002;Diociaiuti et al 2004), can largely Bfit^under the area of two closely packed hydrocarbon chains. For the more complex oligosaccharide polar head groups, slightly more spacing is required, especially at low surface pressures (Maggio et al 1981;Carrer and Maggio 2001).…”
Section: Ceramide-glycosphingolipid Interactionssupporting
confidence: 93%
“…The other conspicuous feature is a broad and diffuse bulge in the isotherm of total axolemma between about 13 mN/m and 30 mN/m. Figure 5b shows the surface potential normalized per unit of molecular surface density (usually denominated surface potential per molecule; see Gaines, 1966;Maggio et al, 1978;Maggio, 1992) as a function of the mean molecular area. The variation of this magnitude with the molecular packing reflects changes in the orientation or the location of dipolar components (Maggio et al, 1978;Maggio, 1992;Beitinger et al, 1989).…”
Section: Surface Behavior Of Axolemma-derived Monolayersmentioning
confidence: 99%
“…The glycosphingolipids were obtained and purified as in [ 1 ]. Glyceryl mono-oleate (99% pure) was from Sigma Chem.…”
Section: Methodsmentioning
confidence: 99%
“…Recently reported studies on the behaviour of gangliosides and neutral glycolipids at the air-water interface revealed that the complexity of the polar head group, and specially the presence of one or more sialic acids, greatly influences their surface properties [1].…”
Section: Introductionmentioning
confidence: 99%